Engineered myocardium model to study the roles of HIF-1α and HIF1A-AS1 in paracrine-only signaling under pathological level oxidative stress. (August 2017) - Acun, Aylin; Zorlutuna, Pinar
Graphical abstract: Abstract: Studying heart tissue is critical for understanding and developing treatments for cardiovascular diseases. In this work, we fabricated precisely controlled and biomimetic engineered model tissues to study how cell-cell and cell-matrix interactions influence myocardial cell survival upon exposure to pathological level oxidative stress. Specifically, the interactions of endothelial cells (ECs) and cardiomyocytes (CMs), and the role of hypoxia inducible factor-1α (HIF-1α), with its novel alternative regulator, HIF-1α antisense RNA1 (HIF1A-AS1), in these interactions were investigated. We encapsulated CMs in photo-crosslinkable, biomimetic hydrogels with or without ECs, then exposed to oxidative stress followed by normoxia. With precisely controlled microenvironment provided by the model tissues, cell-cell interactions were restricted to be solely through the secreted factors. CM survival after oxidative stress was significantly improved, in the presence of ECs, when cells were in the model tissues that were functionalized with cell attachment motifs. Importantly, the cardioprotective effect of ECs was reduced when HIF-1α expression was knocked down suggesting that HIF-1α is involved in cardioprotection from oxidative damage, provided through secreted factors conferred by the ECs. Using model tissues, we showed that cell survival increased with increased cell-cell communication and enhanced cell-matrix interactions. In addition, whole genome transcriptome analysis showed, for the first time to our knowledge, a possible role for HIF1A-AS1 in oxidative regulation of HIF-1α. We showed that although HIF1A-AS1 knockdown helps CM survival, its effect is overridden by CM-EC bidirectional interactions as we showed that the conditioned media taken from the CM-EC co-cultures improved CM survival, regardless of HIF1A-AS1 expression. Statement of Significance: Cardiovascular diseases, most of which are associated with oxidative stress, is the most common cause of death worldwide. Thus, understanding the molecular events as well as the role of intercellular communication under oxidative stress is upmost importance in its prevention. In this study we used 3D engineered tissue models to investigate the role of HIF-1α and its regulation in EC-mediated cardioprotection. We showed that EC-mediated protection is only possible when there is a bidirectional crosstalk between ECs and CMs even without physical cell-cell contact. In addition, this protective effect is at least partially related to cell-ECM interactions and HIF-1α, which is regulated by HIF1A-AS1 under oxidative stress.